1998
DOI: 10.1021/jf9801320
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Bark and Core Lignins from Kenaf (Hibiscus cannabinus)

Abstract: Dioxane and milled wood lignins were isolated from the core and bark of kenaf (Hibiscus cannabinus), variety Salvador. These lignins were characterized by 13C and 1H NMR, FTIR, and UV spectroscopies, permanganate oxidation, and alkaline hydrolysis followed by GC and GC-MS analysis of the released products and by functional groups analysis. The permanganate oxidation and alkaline hydrolysis was also applied to “in situ” lignins. Isolated and “in situ” lignins showed significant differences in composition and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 22 publications
6
30
0
Order By: Relevance
“…Seca et al 10 isolated the dioxane and milled wood lignins (MWLs) from the core and dioxane lignin from the bark of kenaf, which showed that large differences in chemical composition exist between in situ and isolated lignins of kenaf. That is, both the core and bast in situ lignins are rich in the guaiacyl lignin units, whereas the lignins isolated from the core and bast are rich in the syringy lignin units.…”
Section: Introductionmentioning
confidence: 99%
“…Seca et al 10 isolated the dioxane and milled wood lignins (MWLs) from the core and dioxane lignin from the bark of kenaf, which showed that large differences in chemical composition exist between in situ and isolated lignins of kenaf. That is, both the core and bast in situ lignins are rich in the guaiacyl lignin units, whereas the lignins isolated from the core and bast are rich in the syringy lignin units.…”
Section: Introductionmentioning
confidence: 99%
“…In the 13 C-NMR spectra of RL and ILL, the characteristic tertiary carbon resonances from syringylpropane (S) (signals centered at 104.9 ppm) and guaiacylpropane (G) units (signals centered at 111.5 ppm and 119.3 ppm) were observed. The approximately calculated S/G ratios for RL, ILL1, and ILL2 lignins were 1.14, 0.90, and 0.96, respectively, which showed that the RL was richer in syringyl content than the ILL (Seca et al 1998). This may result from the demethoxylation of S units.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 92%
“…On the other hand, aliphatic low-molecular-weight products were obtained in high yields. Seca et al (1998) analyzed kenaf cores and cuticles using various methods and reported that there were strong structural differences in the bark (cuticle) and core lignins in kenaf. Nishimura et al (2002) also analyzed separated kenaf bast, inner bast, and core samples prepared from the top, upper middle, lower middle, and bottom of kenaf stems.…”
Section: Pyrolysis Of Separated Core and Cuticle Kenaf Tissuesmentioning
confidence: 99%